Within-species variation of seed traits of dune engineering species across a European climatic gradient - Del Vecchio, Silvia; Sharma, Shivam Kumar; Pavan, Mario; Acosta, Alicia Teresa Rosario; Bacchetta, Gianluigi; de Bello, Francesco; Isermann, Maike; Michalet, Richard; Buffa, Gabriella (Frontiers in Plant Science, 2022)
Within-species variation is a key component of biodiversity and linking it to climatic gradients may significantly improve our understanding of ecological processes. High variability can be expected in plant traits, but it is unclear to which extent it varies across populations under different climatic conditions. Here, we investigated seed trait variability and its environmental dependency across a latitudinal gradient of two widely distributed dune-engineering species (Thinopyrum junceum, Calamagrostis arenaria). Seed germination responses against temperature and seed mass were compared within and among six populations exposed to a gradient of temperature and precipitation regimes (Spiekeroog, DE; Bordeaux, FR; Valencia, ES; Cagliari, IT, Rome, IT; Venice, IT). Seed germination showed opposite trends in response to temperature experienced during emergence in both species: with some expectation, in populations exposed to severe winters, seed germination was warm-cued, whereas in populations from warm sites with dry summer, seed germination was cold-cued. In C. arenaria, variability in seed germination responses disappeared once seed coat was incised. Seed mass from sites with low precipitation was smaller than that from sites with higher precipitation, and was better explained by rainfall continentality than by aridity in summer. Within-population variability in seed germination accounted for 5% to 54%, while for seed mass it was lower than 40%. Seed trait variability can be considerable both within- and among-populations even at broad spatial scale. The variability may be hardly predictable since it only partially correlated with the analysed climatic variables, and with expectation based on the climatic features of the seed site of origin. Considering seed traits variability in the analysis of ecological processes at both within- and among-populations level may help elucidate unclear patterns of species dynamics, thereby contributing to plan adequate measures to counteract biodiversity loss.